THE ATMOSPHERIC DYNAMICS IN THE SOUTH CENTRAL BRAZIL IN THE SUMMER AND THE INFLUENCE OF THE EL NINO SOUTHERN OSCILLATION (ENSO) - Borsato, Victor da Assunção (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2011)
The atmospheric dynamics of the Central Southern Brazil was studied by means of four weather stations situated in the area of Campo Mourao, PR, Caceres, MT, Brasilia, DF and Caparaó MG in three summers. The summer is characterized by abundant convective rains, mainly in the north of the Tropic of Capricorn. In southern Brazil the interannual variability is increased in years of El Nino and La Nina, and on the region lying north of the tropics there is no accurate information. To investigate the dynamics of air masses that were active in the South-Center of Brazil and the genesis of the rain, weather systems were studied by means of the spatial- temporal patterns. The main aim was to determine the percentage of frontal and convective rainfall and account for the involvement of the air masses in the atmospheric dynamics in the summer, in a climatologic normal year (2008/2009), in a year with the manifestation of the La Nina (2007/2008) and in a year with El Nino (2009/2010). In Caceres and in Brasilia the time of action of the Polar Atlantic mass is limited to sporadic events, while the continental Equatorial mass increases at the same rate. The main consequence of this is the convective rainfall. It was also found that for Campo Mourao and Caparaó the frontal systems, the Polar Atlantic and the Atlantic Tropical masses contributed actively to the types of weather. Although there are few researches regarding this theme, in this study it was found that in the summer of 2007/2008, of La Nina event, the rainfall was higher.